2010
DOI: 10.4103/0975-3583.70903
|View full text |Cite
|
Sign up to set email alerts
|

Silent myocardial ischemia in prediabetics in relation to insulin resistance

Abstract: Background:Myocardial perfusion imaging (MPI) is a powerful diagnostic and prognostic tool for evaluating coronary artery disease (CAD). Several studies have shown Type 2 diabetics are at increased risk for having CAD. In addition, insulin resistance is generally considered to be of major importance in the pathophysiology of Type 2 diabetes mellitus. However, the area of screening prediabetics for CAD remains unclear. Given that glucose intolerance and insulin resistance precede the development of overt diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The presence of prediabetes increases the risk of developing type 2 diabetes mellitus (T2DM) 3-fold to 10-fold [1]. In addition, previous studies have reported that there are cause–effect relationships between prediabetes and cardiovascular disease such as coronary heart disease or stroke, and all-cause mortality [2,3,4,5]. According to the World Health Organization, and depending on the diagnostic criteria used (e.g., age, ethnicity, sex, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of prediabetes increases the risk of developing type 2 diabetes mellitus (T2DM) 3-fold to 10-fold [1]. In addition, previous studies have reported that there are cause–effect relationships between prediabetes and cardiovascular disease such as coronary heart disease or stroke, and all-cause mortality [2,3,4,5]. According to the World Health Organization, and depending on the diagnostic criteria used (e.g., age, ethnicity, sex, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is a well-known risk factor for CAD (11,12) . Beyond that, more cardiovascular event occurrence is reported with elevating blood glucose levels (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Population-based studies report an increased rate of macrovascular complications and mortality in pre-diabetes; and fasting plasma glucose, postprandial plasma glucose and HbA1c are related with increased mortality independent of obesity, hypertension and lipid profile (17,18). Nasr and Sliem (19) reported that pre-diabetics have myocardial defects, which represent a pattern of cardiovascular risk. In our study, the prevalence of hypertension, hypertriglyceridemia and use of statins were more common in the diabetic group as compared to pre-diabetics.…”
Section: Discussionmentioning
confidence: 99%